The Good Fill - A Unique “Zero Waste” Business Deals With Unexpected Success and Potential Expansion Opportunities - Bamber, Joseph; Holaway, Rick; Ivey, Joe (American Journal of Management, 2020)
This case study follows a female social entrepreneur on her journey as she starts a zero-waste retail business with unexpected press and success. Based on interviews with the entrepreneur and her family, this case puts students in the decision-making process, considering questions of purpose, sustainability, opportunities, and work-life balance. The case features an accompanying website with press articles, videos, case timeline, financial documents, product prices, and other resources. The case is intended to be taught in a team format with teams advocating for a potential scenario. This case is suitable for students in upper class courses in strategy, management, entrepreneurship, or social entrepreneurship.